The effects of voluntary GDPR adoption and the readability of privacy statements on customers' information disclosure intention and trust. Issue 2 (20th November 2019) - Zhang, Yibo; Wang, Tawei; Hsu, Carol
Abstract : Purpose: The purpose of this paper is to examine the impacts of companies' voluntary adoption of the General Data Protection Regulation (GDPR) as well as the readability of privacy statements on US customers' intention to disclose information and their trust in a company. Design/methodology/approach: Building on the construal level theory and psychological distance, the authors conduct a 2 × 2 + 2 between-participants experiment with 255 participants. Findings: The findings show that a company's voluntary adoption of the GDPR has positive effects on customers' intention to disclose information to and their trust in that company. In addition, the effects of GDPR adoption are stronger when the adopting company's privacy statements possess a higher level of readability. Originality/value: The authors believe this study poses policy implications for the outcomes of GDPR adoption and the recent debate on both a stricter data breach and privacy regulation.